The Characteristics of Sociodemography, Histopathologic Features, Stage, and Management of Ovarian Cancer in Dr. Ramelan Navy Hospital Surabaya - Rahmalia, Karina; Sudiarta, Ketut Edy; Setianingsih, Herin; Diarsvitri, Wienta (http://dharmais.co.id/, 2024)
Background: Ovarian cancer is considered a silent killer disease, mainly due to the late diagnosis. It is often diagnosed at an advanced stage, thus increasing the mortality rate. Ovarian cancer can happen to any age, with different characteristics according to the age group, the most often being the epithelial type.Methods: This research is a descriptive study with a quantitative method. This study aims to determine the characteristics and histopathological features of ovarian cancer in Dr. Ramelan Navy Hospital from January 2019 to December 2021. There were 155 samples out of 635 patients, with the information acquired through medical records.Results: The highest incidence of ovarian cancer occurs in the 40-60-year-old group at 52.9%. Among all participants, 85.8% of patients were not employed. Of most histopathological features in epithelial ovarian cancer, 34.8% were the serous carcinoma subtype. The majority of these cases were diagnosed at stage IIIC at 21.3%, and the most prevalent treatment for ovarian cancer was surgery and chemotherapy at 49.7%.Conclusions: The most common type of ovarian cancer is epithelial ovarian cancer, a subtype of serous carcinoma, with histopathological features of round nucleated anaptic cells, prominent nucleoli, forming acini, papillae, and thin connective tissue stroma.